UTILIZATION OF TECHNOLOGY IN NGAJI METHODS IN THE MIDST OF A PANDEMIC - Aulia Norma Lita (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2021)
In a pandemic condition like this, technological developments can not be released from the development of the community itself, especially in Pesantren. This research aims to see the utilization of technology in Ngaji method in Pesantren that is in Java at the time of pandemic. Methods used are qualitative descriptive with the technique of collecting data using nonpartsipative observation through observation. Research Data in the form of posters, drawings, and writings found on social media. The results of the study amounted to 22 data, with the specification of 16 Pesantren using a method of Bandongan, 2 using Sorogan, 3 Islamic boarding methods Wetonan, and 4 Pesantren using a dual method of Bandongan and discussion. The results showed that boarding schools participated in utilizing technology as a step and effective solution in the process of paying in the center of pandemic.Keyword: Technology, Ngaji method, pandemic